Straits settlements laws [1936-1939] (Petaling Jaya : Arkib Negara)
Mengandungi Supplements to the laws of the Straits Settlements Part I termasuk Ordinance no. 10 of 1936 Revised Edition of the Laws (annual supplements); Ord. no. 41 of 1936 Statute Law (Revised Edition (Amendment); Chapter 6 Labuan (amendment) [11th March 1938]; Cap 30 Common Gaming Houses (amend.); [10th Dec 1937]; Cap 38 Youthful Offencers, Reception (Amend.); [20 Nov. 1936] Cap 43 Crown suits (Amend.) [1th March 1938]; Ordinance no. 1 of 1936 Silver Jubilee Fund (Singapore); Ord. No. 12 of 1936 Registration of Aliens; Ord. no. 38 of 1936 Trade Marks; Chapter 33 Women and Girlds Protection (Amendt). [2nd Jul. 1937; 15th Dec. 1939].